Innovative pathways for university entrepreneurship in the 21st century - Hoskinson, Sherry; Kuratko, Donald F. (Advances in the study of entrepreneurship, innovation and economic growth, 2014)
The complex global environment for entrepreneurship has experienced significant change during the past decade. University based entrepreneurship is at the nexus of this environment. Students and faculty of entrepreneurship are uniquely positioned as agents in the movement of discovery and innovation.